Algorithms and discrete applied mathematics : third International Conference, CALDAM 2017, Sancoale, Goa, India, February 16-18, 2017, Proceedings /: third International Conference, CALDAM 2017, Sancoale, Goa, India, February 16-18, 2017, Proceedings. (2017) - Unknown
No abstract available